Impacto da implantação da Usina Hidrelétrica Luís Eduardo Magalhães (UHE Lajeado) no rio Tocantins, com ênfase na comunidade bentônica - Kikuchi, Regina Mayumi (Universidade Federal de São Carlos, 2005)
This work aims to evaluate the impact and influence of the Luís Eduardo Magalhães hydroelectric power station (Lajeado Dam) in Tocantins River, which is located in the municipal district of Miracema of Tocantins TO, Brazil, through benthic macroinvertebrates community study in pre-flooding, reservoir filling and post-filling Phases. The samples have been collected with the help of a suction sampler in seven different points (at reservoir's upstream, downstream of the dam and five points in the reservoir), every other month totalling fifteen collections during a period of thirty months. The impact in the reservoir has been confirmed as due to environmental changes. These alterations are dynamic and vary in function of the dam proximity, seasonal changes and gate operations, causing modifications on density and richness of the organisms, reducing or enhancing them. The impact at the downstream of the dam has been noticed as well, probably due to the quality of the water released from the dam and the dam operation itself. Also at the control point on the reservoir's upstream, the impact with a prevalence of an invasive freshwater species in terms of density has been confirmed. With the construction of the dam, the invasive mollusks of the gên. Corbicula sp. prevail in density terms on the upstream point (Balsas) and in the beginning of the reservoir (Ipueiras point). In the reservoir, invertebrates like Ephemeroptera, Trichoptera, Plecoptera, Coleoptera, Diptera (Simuliidae and Empididae) has disappeared mainly in the dam s closest points (Graciosa and Todos os Santos) and the Diptera larvae (Chaoboridae and Chironomidae - Tribo Chironomini) has prevailed. In the downstream point (Gorgulho) some groups of invertebrates like Diptera larvae (Simuliidae) and Plecoptera has disappeared and Chaoboridae larvae of the reservoir appear mainly in the rainy period at this point. This work confirms that there have been alterations on the composition and structure of the benthic community due to environmental changes (mainly on the dissolved oxygen in water, depth of the dam, current speed and type of substratum) caused by the construction of a hydroelectric power station. A crescent longitudinal gradient of impact from the riverine zone to the lacustrine zone of reservoir has been confirmed.
Keywords: Ecologia de rios; Biomonitoramento; Macroinvertebrados; Impacto ambiental - barragens; Reservatórios; CIENCIAS BIOLOGICAS::ECOLOGIA